2018
DOI: 10.1007/s10488-018-0867-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Assignment of Therapeutic Homework in a Large Public Children’s Mental Health System

Abstract: Therapeutic homework is a fundamental skill-building component of the majority of evidence-based therapies and is associated with better treatment outcomes. However, it is rarely utilized in public mental health settings. To determine barriers to homework use and identify predictors of clinicians' assignment of homework, an online survey was administered to 267 clinicians in a large diverse public mental health system. Clinicians who were younger, licensed, whose supervisors asked about homework and whose clie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Findings from the present study suggested that many of the between-session activities completed by respondents were specific in nature. This suggests that the clients did something intentional, rather than a vague sense of having “done something.” Skills-building tasks were common as were practical applications of in-session tasks, as has been found by others (e.g., Kelly & Deane, 2011; Trask et al, 2018). The target of the homework was nearly equally split between couples and individuals, suggesting that participants, while in couple therapy, were also engaged in some personal development.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Findings from the present study suggested that many of the between-session activities completed by respondents were specific in nature. This suggests that the clients did something intentional, rather than a vague sense of having “done something.” Skills-building tasks were common as were practical applications of in-session tasks, as has been found by others (e.g., Kelly & Deane, 2011; Trask et al, 2018). The target of the homework was nearly equally split between couples and individuals, suggesting that participants, while in couple therapy, were also engaged in some personal development.…”
Section: Discussionmentioning
confidence: 74%
“…Between-session tasks have evolved as a skill-building component of several evidenced-based models of therapy (e.g., cognitive behavioral therapy, integrative behavioral couples therapy, etc. ; Trask et al, 2018). Common examples of therapeutic homework from evidence-based models include exercises for affect recognition, relaxation techniques, and exposure to anxiety-provoking situations (Hudson & Kendall, 2002).…”
Section: Psychotherapeutic Homeworkmentioning
confidence: 99%